SOSIALISASI PROBLEM SOLVING KLAIM BPJS DI RUMAH SAKIT - Harris Rambey; Irmayani Irmayani; Delita Br Panjaitan; Arif Sudjatmiko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Indonesia as a welfare state aims to realize public welfare. This underlies the development of social security by the Indonesian government, which one is through health insurance. In Practice, the goal of creating BPJS is not compatible with reality, provable by a wide variety of issues that are difficult to solve. One of them is the problem with the management of claims for the BPJS. As for the subject of this study is health insurance, specifically management claims. The study uses normative legal research methods to adopt a statute approach, a conceptual approach, and a case approach. Studies have shown that despite efforts by the government to address the problem, but those efforts didn’t work because of some inhibitory factors. Needed solutions to the formation and application of the IMP (Identity Monitoring Program) concept and it is integrated with Disduk Capil to BPJS. The concept of IMP’s implementation is expected to a minimized deficit on BPJS and solving gone of the causes problems is claim management.